Secondary school pupils' understanding of equation solving - Ng, Soh Hua. (2009)
In assessing pupils, teachers are more concerned with whether pupils are successful at performing a certain mathematical task. Errors that pupils make in performing the task are often overlooked. However, pupils' errors can reveal much about pupils' difficulties in performing the mathematical task. This wealth of information is often left untapped as teachers cannot afford the time to analyse and interpret pupils' errors.